2014
DOI: 10.1002/eat.22284
|View full text |Cite
|
Sign up to set email alerts
|

Parents and prevention: A systematic review of interventions involving parents that aim to prevent body dissatisfaction or eating disorders

Abstract: Although a greater focus on engaging and retaining parents is needed, this review demonstrates that a small number of prevention studies with parents have led to significant reductions in risk of body image and eating problems, and future research is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
76
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 63 publications
3
76
0
11
Order By: Relevance
“…Importantly, interventions targeting parents can harness the powerful protective role parents can play by equipping them with tools to use with their children to foster positive body image. This could include helping their children to develop media literacy in order to resist appearance-related sociocultural pressures, and focusing on non-appearance related attributes and achievements (Hart, Cornell, Damiano, & Paxton, 2014). Such interventions also provide an opportunity to support parents to develop their own positive body image, so that they are better able to role model positive body image behaviours and attitudes to their children.…”
mentioning
confidence: 99%
“…Importantly, interventions targeting parents can harness the powerful protective role parents can play by equipping them with tools to use with their children to foster positive body image. This could include helping their children to develop media literacy in order to resist appearance-related sociocultural pressures, and focusing on non-appearance related attributes and achievements (Hart, Cornell, Damiano, & Paxton, 2014). Such interventions also provide an opportunity to support parents to develop their own positive body image, so that they are better able to role model positive body image behaviours and attitudes to their children.…”
mentioning
confidence: 99%
“…Furthermore, recent review papers share a common idea that there are no particular patterns in family functioning associated with eating disorders; rather, family functioning is diverse (Holtom-Viesel & Allan, 2014;Konstantellou, Campbell, & Eisler, 2012;Le Grange, Lock, Loeb, & Nicholls, 2010). Invariably, these researches also agree that family has an important role to play in the development of disordered eating behaviors (Hart, Cornell, Damiano, & Paxton, 2015;Konstantellou et al, 2012;Le Grange et al, 2010;Steinberg & Phares, 2001), and that attention should be given to potential areas in the family that may work as protective factors and are key for prevention and intervention (Konstantellou et al, 2012;Steinberg & Phares, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They can foster positive body image among their daughters by modelling positive attitudes and behaviours towards their own appearance (Abraczinskas, Fisak, & Barnes, 2012). To an extent, they can also protect their daughters from sociocultural appearance pressures (e.g., helping them to deconstruct unhelpful media messages) (Hart, Cornell, Damiano, & Paxton, 2015). Alternatively, maternal pressures on daughters to lose weight and appearance-related criticism prospectively predict body dissatisfaction and disordered eating among daughters (Francis & Birch, 2005;Presnell, Bearman, & Stice, 2004).…”
mentioning
confidence: 99%
“…A recent systematic review of studies conducted between 1992-2013 found that involving parents in interventions designed to improve children's body image and prevent disordered eating can be effective (Hart et al, 2015). Of the twenty studies reviewed, three studies were sufficiently methodologically rigorous to isolate the effect of parental involvement on outcomes among children.…”
mentioning
confidence: 99%
See 1 more Smart Citation